Synchronous palynofloristic extinction and recovery after the end-Permian event in the Prince Charles Mountains, Antarctica: Implications for palynofloristic turnover across Gondwana - Lindström, Sofie; McLoughlin, Stephen (Review of Palaeobotany and Palynology, 2007)
In the Prince Charles Mountains (PCMs) the conformable Permian-Triassic (P-T) succession is characterised by an abrupt transition from coal-bearing to coal-lacking strata, which coincides with the demise of the Permian Glossopteris-dominated flora. About 32% of the typical Permian spores and pollen are registered for the last time in the uppermost coal. Throughout the earliest Triassic an additional 34% of the lingering Permian taxa disappear, while pioneering typical Triassic taxa appear. This interval of contemporaneous stepwise extinction and recovery resulted in an actual increase in spore-pollen taxa diversity during the earliest Triassic. The estimated average sedimentation rate indicates that the 24 m sampling gap that separates the last Permian assemblage from the first Triassic one represents ca 96000 years, and that the continued stepwise extinction and recovery lasted for ca 325 000 years. In the aftermath of the end-Permian crisis only 27% of the typical Permian spores and pollen, that were present from the lower McKinnon Member in the Prince Charles Mountains survived to the late Induan, but by then the biodiversity had only decreased by less than 10%. Comparisons of Gondwanan palynological and lithological data indicate that intense global warming had already begun in the Permian, and that high latitude Gondwana areas such as the PCMs, were affected later than areas to the north and west. They also suggest that the end-Permian crisis affected the various Gondwana regions in different ways, but that the end result appears to have been a more equable, sub-humid to semi-arid, and less seasonal climate across southern Gondwana.